#### Answer

$H(y) = ln(y)+c$

#### Work Step by Step

$h(y)=y^{-1}$
$\int h(y)dy = \int y^{-1}$
$H(y) = ln(y)+c$

Published by
Pearson

ISBN 10:
0321947347

ISBN 13:
978-0-32194-734-5

$H(y) = ln(y)+c$

$h(y)=y^{-1}$
$\int h(y)dy = \int y^{-1}$
$H(y) = ln(y)+c$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.